Routing in WDM based wireless mesh networks with capacity estimation. (8th June 2012) - Kumar, Neeraj; Chilamkurti, Naveen; Kim, Jongsung
In order to support and provide resources to various applications, in this paper, we propose a dynamic dynamic routing for WDM based wireless mesh networks (WMNs). To choose an optimised route, cost metric (CM) and load utilisation matrix (LUM) are constructed dynamically. Using LUM, load utilisation rating (LUR) for each link is calculated. At last, CM is calculated from LUR. The minimum value of CM is chosen to construct the path between source and destination. The value of CM is compared with existing hop count metric. The proposed algorithm is simulated on two well-known WDM-based networks, NSFNet and EON. The results obtained show that the proposed algorithm is quite effective to route the packets to less congested path and has higher throughput and less blocking probability than the other proposed algorithms.